Marko Jesenšek: The Slovene Language in the Alpine and Pannonian Language Aria. The history of the Slovene Language.: Kraków: Towarzystwo Autorów i Wydawców Prac Naukowych Universitas, 2005. 365 str. - Ulčnik, Natalija (Slavia Centralis, 2020)
Avtorica prispevka predstavlja monografijo The Slovene Language in the Alpine and Pannonian Language Aria s podnaslovom The history of the Slovene Language avtorja Marka Jesenška.
Keywords: monografija; Marko Jesenšek; The Slovene Language in the Alpine and Pannonian Language Aria; The history of the Slovene Language; prekmurski knjižni jezik; vzhodnoštajerski knjižni jezik